Implementation and evaluation of the Forro stream cipher in Tofino programmable hardware for remote attestation in datacenters - Pierini, Rodrigo Alexander de Andrade; Teixeira, Caio; Esteve Rothenberg, Christian Rodolfo; Amaral Henriques, Marco Aurélio (Journal of the Brazilian Computer Society, 2026)
The software-defined networking (SDN) paradigm has enabled several innovations in computer networking, specially in programmable packet processing. This paper shows the feasibility and impact on computing resources of the Forro stream cipher algorithm in the Tofino programmable hardware switch. For comparison purposes, the ChaCha algorithm was also analyzed in terms of its performance and impact on the same device. It was observed that the Forro algorithm performs better and uses fewer resources than ChaCha in sequential implementations. However, when parallelization techniques are adopted, ChaCha performs better for higher data rates, but uses more ternary matching resources than Forro. For the use case of remote attestation in programmable data planes, the Forro cipher seems more promising, as it uses less limited resources and can achieve sufficient throughput rates for this scenario. We then propose P4DRA, a distributed remote attestation solution based in the programmable data plane that can offload the verification process of remote devices to the data plane, freeing resources from a central verifier based on a x86 server and improving the attestation proof verification speed by around 150 times.